PENDIDIKAN ISLAM MENURUT KH. HASYIM ASY’ARI (Analisis Kritis Kode Etik Murid Terhadap Guru) - Muhammad Furqan; Sakdiah; TR Keumangan (PENDALAS: Jurnal Penelitian Tindakan Kelas dan Pengabdian Masyarakat, 2021)
Abstract. Students, will not have the success of science and will not benefit from the knowledge they have, other than if they want to glorify the knowledge itself, respect the experts and exalt it. It is explained that a person will achieve success if he himself glorifies something he is looking for; so too is a person's failure because he does not want to glorify something he is looking for. According to KH. Hasyim Asy'ari in the Book of Adab Al-'Alim wal Muta'allim, the ethics of a student towards his teacher is divided into 12 ethics, namely: choosing an educator figure; looking for competent teachers; obey the educator; glorify educators; fulfill the rights of educators; positive thinking in educators; pay attention to karma when meeting educators; manners when sharing the room with educators; arranged karma on the opinion of educators; show a happy attitude and enthusiasm for learning; pay attention to manners when communicating; arranged karma in educators in all situations and conditions. KH thinking Islamic education. Hasyim Asy'ari is very relevant when placed in modern times today. The learning process takes a long and gradual one. Science will not easily apply our hearts are still dirty with immoral actions. We need to purify our hearts to learn, so that what our hearts can accept and can easily be applied in actions that reflect good morals. Every action depends on the intention. Thus it is clear from the viewpoint of Islam that students have an obligation to follow the rules or norms that are in accordance with the National Education System Law No. 20 of 2003 article 12 paragraph 1. to ensure the continuity of the process and education.